3D Printing—Encompassing the Facets of Dentistry - Oberoi, Gunpreet; Nitsch, Sophie; Edelmayer, Michael; Janjić, Klara; Müller, Anna Sonja; Agis, Hermann (Frontiers in Bioengineering and Biotechnology, 2018)
This narrative review presents an overview on the currently available 3D printing technologies and their utilization in experimental, clinical and educational facets, from the perspective of different specialties of dentistry, including oral and maxillofacial surgery, orthodontics, endodontics, prosthodontics and periodontics. It covers research and innovation, treatment modalities, education and training, employing the rapidly developing 3D printing process. Research-oriented advancement in 3D printing in dentistry is witnessed by the rising number of publications on this topic. Visualization of treatment outcomes makes it a promising clinical tool. Educational programs utilizing 3D-printed models stimulate training of dental skills in students and trainees. 3D printing has enormous potential to ameliorate oral health care in research, clinical treatment and education in dentistry.